2011
DOI: 10.1007/s11858-011-0328-3
|View full text |Cite
|
Sign up to set email alerts
|

The use, nature and purposes of measurement in intermediate-level occupations

Abstract: To provide a basis for thinking through how measurement can be taught in schools, this paper analyses the use, nature and purposes of measurement in intermediate-level work, i.e. occupations for which a school-level qualification is required, but not a bachelor degree or higher. In the Netherlands, senior secondary vocational education (MBO) prepares its students (aged 16?) for intermediate-level work. An initial analysis of the use and purposes of measurement was based on competence descriptions for 549 MBO-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Teachers and supervisors confirmed that much of the work that lab technicians eventually do is in between what the qualification files of lab technician and allround operating technician demand. Yet it is well possible that the manual work with relatively old machines at school is good preparation for the more automatic work in workplaces with the newest machines-this is at least what several teachers in other settings told us (Bakker et al 2011b).…”
Section: Promoting Continuity In Vocational Learningmentioning
confidence: 99%
“…Teachers and supervisors confirmed that much of the work that lab technicians eventually do is in between what the qualification files of lab technician and allround operating technician demand. Yet it is well possible that the manual work with relatively old machines at school is good preparation for the more automatic work in workplaces with the newest machines-this is at least what several teachers in other settings told us (Bakker et al 2011b).…”
Section: Promoting Continuity In Vocational Learningmentioning
confidence: 99%
“…Students have to know the basics, but should not perform complex calculations that computers can do instantly by hand. To understand underlying software and to uncover the black box, it can be useful to use mechanical tools as an intermediate step to digital technology (Bakker, Wijers, Jonker, & Akkerman, 2011). The Advisory Committee on Mathematics Education (2011) states that employers think employees should study mathematics at a higher level than they use in their practices to provide them with confidence and versatility to use mathematics in new situations at work.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Students often learn measurement procedures (Lee & Smith, 2011), but rarely do they grapple with the foundational conceptual problem of how to establish coordination between the objects and relations of a particular phenomenon, its structure, and with the corresponding symbolic, and often material, objects and relations of its measure. This ''black box'' quality of measure is often true of workplaces as well, where the very success of the tools employed tend to obscure the origins of the correspondences established between measure and phenomena (Bakker, Wijers, Joinker & Akkerman, 2011). Yet research in mathematics education suggests that even young students can be supported to investigate and understand relations between characteristics of space, such as length and area, and aspects of their measure, such as unit and scale (e.g., Clements & Bright, 2003).…”
Section: Introductionmentioning
confidence: 99%